Celts and La Tene Culture – a View From Periphery - Potrebica, Hrvoje (Array, 2012)
In early stages of Croatian prehistoric archaeology 'Celts' were perceived as more or less defined ethnic group whose migration into these areas brought about significant and deep change in the material culture of the Late Iron Age. Since Croatia is located on periphery of the ‘Celtic world’, the material culture as well as some features of social organisation recognized as ‘Celtic’, were always considered to be initially foreign element coming from outside and fundamentally changing inner structure and cultural identity of local population. However, soon it became obvious that some elements of ‘Celtic’ material culture reached local Iron Age communities before they became part of the La Tene cultural complex. At that point the concept of the La Tene Culture was widely accepted and used to mark the difference between material culture and actual ethnic groups, although the ‘Celts’ were always considered as population indigenous to this cultural phenomena. On the other hand, closer examination of local cultural groups revealed that the fundamental structural change of Hallstatt communities in this area took place before any of La Tene features reached this area. Towards the end of the 6th century B.C. rich graves and tumuli disappeared from the Eastern Hallstatt Circle and many centres of local elites that were active for centuries apparently ceased to be central points of communication and/or economic network. However, it seems that some of these central places continued to operate on some level and that local communities were not wiped out but rather underwent significant transformation which was far more complex process than we are able to perceive at this point. While concept of ‘Celts’ emerged from the Western Hallstatt Circle as more or less result of cultural evolution, in the southeastern Pannonia the situation was significantly different. It is not the question of chronological as much as contextual shift. Early La Tene finds are also present in this area, but the context and semantic value of these finds are different than in the central ‘Celtic’ area. Another important point is that the mechanism of transfer as well as acceptance of the Early La Tene elements into local cultures is significantly different from the process that takes place in later periods of the Late Iron Age when this area is occupied by compact La Tene communities that originated as some sort of amalgam made of local communities and incoming groups of people that were recognized as ‘Celts’. The situation is even more complicated if we have in mind the fact that both of those groups, ‘local’ as well as incoming ‘Celts’, were to some extent exposed to the La Tene Culture before they were merged into compact and recognisable cultural item. It is obvious that we have to differentiate between processes of ‘Celtization’ and ‘Latenization’, but due to specific cultural dynamics of local communities in this area, they are more processual categories, each of them comprising of at least several models.